Organizational learning capability, procedural justice and job performance among Royal Malaysian Air Force air craft technicians - Akhbar Khan, Bibi Zarjaan (2011)
Since Independence to the present, Malaysia has undergone a rapid period of technological, economic and social change; heading towards Vision 2020 is expected to be even more rapid and stressful. Organizations that are able to visualise the future will be able to sustain themselves through rapid changes by gradually shifting their strategies to flow according to the environmental changes. By doing so, they would have a competitive advantage in the industry. The key factor for the organizations to compete and sustain themselves is learning, specifically organizational learning, as this will enable the workforce to improve their competency and efficiency,and thus promote organizational effectiveness. Organizational learning is no longer exclusive to the private sector, and it is increasingly emerging as a vital strategy in the public sector. The Royal Malaysian Air Force, as part of this sector, has already inculcated the Kforce (knowledge force) as part of this strategy: the intention is develop their organization into an internationally competitive entity. The purpose of this study is to determine the effect of organizational learning capability on job performance and perceptions of procedural justice among the aircraft technicians in the Malaysian Air Force Flying Squadrons. In addition, this study seeks to determine the role of procedural justice as a mediating variable in the relationship between organizational learning capability and the aircraft technician’s job performance. The population of the study is about 1150 aircraft technicians working in 16 Air Force squadrons in Malaysia. Primary data is collected via questionnaires administered to 290 aircraft technicians chosen by proportionate sampling procedure. A total of 235 answered questionnaires were returned and used in the final analysis. The constructs used in this study are organizational learning (Gomez et al.,2004), procedural justice (Niehoff and Moorman, 1993) and job performance (Suliman, 2001). The reliability and validity of the instrument are established via Cronbach’s alpha. SPSS Version 16 is used to analyse the data quantitatively to provide evidence for model testing and the presence of mediation effect within the relationships between independent and dependent variables. Sobel’s z-test concludes the analysis to verify the presence of mediation effect. The study reveals that the level of organizational learning, procedural justice and job performance are rather high among the aircraft technicians. Organizational learning capability is positively related to perception of procedural justice and job performance among them. Procedural justice is also positively related with job performance and this variable partially mediates the relationship between organizational learning capability and job performance.